DEVICE AND METHOD FOR CONTROLLING A SYSTEM HAVING UNCENTRITY IN THE DYNAMICS THEREOF - BENOSMAN MOUHACINE; RUSSELL RICHARD; VAN BAAR JAKOB (2023)
A controller is provided for controlling a system having uncertainty in its dynamics subject to constraints on the operation of the system. The controller is configured to obtain historical data of operation of the system and determine, for the system in a current state, a current control action to transition a state of the system from the current state to a next state. The current control action is determined from a robust and constrained Markov decision process (RCMDP) that uses the historical data to optimize the performance cost of the operation of the system subject to optimization of the safety cost at which the constraints are applied to the operation of the system, a state transition for each of the performance cost and the safety cost is represented by a plurality of state transitions that capture dynamic uncertainty of the system. 提供了一种用于控制受制于对系统的运行的约束的在其动态中具有不确定性的系统的控制器。所述控制器被配置为获取所述系统的运行的历史数据，并且对于处于当前状态的所述系统，确定将所述系统的状态从所述当前状态转变为下一状态的当前控制动作。根据鲁棒和约束马尔可夫决策过程(RCMDP)来确定所述当前控制动作，所述鲁棒和约束马尔可夫决策过程(RCMDP)使用